A novel method of stick-slip vibration composite driving for improving the step displacement. (15th October 2018) - Zhu, Jie; Zhong, Bowen; Jin, Ziqi; He, Haidong; Wang, Zhenhua; Sun, Lining
Abstract: The piezoelectric-actuated inertial stick-slip device (PAISSD) is widely used in the field of nanotechnology because of its high resolution and theoretically unlimited displacement. However, the small step displacement is an unavoidable issue of stick-slip driving technology. In this research, a stick-slip vibration composite driving method (SSVCDM) is proposed to increase the step displacement. The SSVCDM combines the principle of inertial stick-slip driving and the friction reduction under vibration. The friction is greatly affected by the vibration waveform when the PAISSD is in the buffer period. First, the SSVCDM is proposed, which includes a second order driving waveform, the step response of the waveform and the vibration waveform. Then the mechanism and the effect of friction reduction under vibration are studied based on the inertial stick-slip driving. Finally, the mechanism and the effect of friction reduction under vibration is validated and the effectiveness of the SSVCDM is demonstrated via experimental studies. The results provide an insight into the development of friction reduction technology by the inertial stick-slip driving.